Strategi Guru dalam Menghadapi Isu Keamanan Siber dalam Pembelajaran Online - Nur Hasanah; Aisyah Mutiara Sani; Sri Wardani; Muhammad Hasyimsyah Batubara (Yayasan Al-Afif, 2026)
The development of online leaming has provided easier access to information, but at the same time has increased cybersecurity risks in educational environments, especially in areas with limited infrastructure, such as Mandailing Natal Regency. This study aims to analyze teachers' strategies in addressing cybersecurity issues in online learning in the region. The research employed a qualitative approach using a phenomenological method and was conducted in Mandailing Natal Regency from January to March 2025. The participants consisted of eight teachers. who actively used online learning platforms and had experienced cybersecurity-related problems. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the interactive analysis model of Miles and Huberman, strengthened by source and method triangulation. The findings revealed that the main cybersecurity threats included account misuse, leakage of students' personal data, weak password usage, and potential phishing attacks through unknown links. To address these challenges, teachers implemented strategies such as improving digital literacy, using relatively secure platforms, supervising students' online activities, promoting digital ethics education, and adapting to technological developments, although these efforts were constrained by limited internet access, inadequate devices, and lack of formal training. These findings indicate that cybersecurity. strategies in online learning in Mandailing Natal are adaptive and contextual, highlighting the need for stronger. policy support and better facilities from schools and local governments.